2022
DOI: 10.1161/circinterventions.121.011110
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in Adult Patients With Pulmonary Hypertension After Percutaneous Closure of Atrial Septal Defects

Abstract: Background: Pulmonary hypertension (PH), recently redefined as mean pulmonary arterial pressure >20 mm Hg (PH 20 ), may be observed in patients with atrial septal defects (ASD). We aimed to determine the effect of preprocedural PH 20 status on outcomes among patients undergoing ASD closure. Methods: Study population was selected from a retrospective registry of adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
6
1
Order By: Relevance
“…Our study confirmed that ASD patients with PH had higher mortality and suffered more often from mitral and tricuspid regurgitation and arrhythmias, compared to patients without PH. This is in line with the literature; patients with PH had more comorbidities, were older and had a significantly higher risk of developing major cardiac and cerebrovascular adverse events after transcatheter ASD closure ( 25 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our study confirmed that ASD patients with PH had higher mortality and suffered more often from mitral and tricuspid regurgitation and arrhythmias, compared to patients without PH. This is in line with the literature; patients with PH had more comorbidities, were older and had a significantly higher risk of developing major cardiac and cerebrovascular adverse events after transcatheter ASD closure ( 25 ).…”
Section: Discussionsupporting
confidence: 90%
“…Pulmonary hypertension (PH) represents an important risk factor associated with reduced functional capacity and increased mortality in patients with atrial septal defect (ASD) (1)(2)(3)(4)(5)(6). Moreover, persistence of PH after ASD closure is strongly associated with increased mortality (4,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The optimal management of patients with ASD and PAH is controversial [2,3]. When the PAH is severe, surgical closure has produced poor outcomes [4][5][6], whereas transcatheter closure after lung transplantation (transplant-and-repair strategy) has been found beneficial [7].…”
mentioning
confidence: 99%
“…The 2022 ESC/ERS guidelines stipulate that ASD closure should be considered only when pulmonary vascular resistance (PVR) is below 5 Wood units (WU) [3]. However, transcatheter shunt closure seems possible in selected patients with higher PVR values, particularly after PAH-specific treatment (PAHST) (treat-and-repair strategy), although the data come only from small cohorts and current recommendations rely primarily on expert opinion [6,[8][9][10]. Prospective studies are needed to further assess this strategy.…”
mentioning
confidence: 99%